High dose hepatitis B vaccine is not effective in patients using immunomodulatory drugs: a pilot study - Asli Haykir Solay; Fatma Eser (Taylor & Francis Group, 2019)
In patients undergoing immunotherapy, the quality of the immune response is reduced, which may negatively affect the efficacy of vaccination. This study was conducted in order to evaluate the efficacy of the hepatitis B virus (HBV) vaccine in patients using immunomodulators. Seronegative patients for HBV who were using biological agents, were included in the study. The vaccination was administered on the standard schedule in 3 doses of 20 or 40 µg/ml. Eighty-two patients (52%) were males and the mean age of all patients was 44,8 ± 10,3 years. Among these 109 patients, 83 had psoriasis, 12 had Crohn's disease, six had rheumatoid arthritis, three had ulcerative colitis, three had hydradenitis supurativa, one had Behcet's disease and one had ankylosing spondylitis. The biological agents that were being used by these patients were adalimumab (62), ustekinumab (25), infliximab (12), etanercept (9) and golimumab (1). Seventy-three of the patients were vaccinated with a dose of 20 µg/ml and 36 with 40 µg/ml. The anti-HBs titers of fifty-eight (53.2%) patients were above 10 mIU/ml. The antibody response rate was lowest in infliximab-users (16.7%) (p = 0.007), which was followed by adalimumab (48.4%), and higher protection rates were achieved in patients using ustekinumab and etanercept (72% and 88.9%, respectively; p < 0.05). The HBV vaccine response rate in patients using immunomodulators was significantly lower than that in immunocompetent patients. Furthermore, high dose vaccination did not increase the response rate. Clinicians should take into account administering HBV vaccination before treatment with biological agent in patients who have negative HBV serology.